2021
DOI: 10.3390/en14113095
|View full text |Cite
|
Sign up to set email alerts
|

SHP Assessment for a Run-of-River (RoR) Scheme Using a Rectangular Mesh Sweeping Approach (MSA) Based on GIS

Abstract: This work proposed a base method for automated assessment of Small Hydro-Power (SHP) potential for a run-of-river (RoR) scheme using geographic information systems (GIS). The hydro-power potential (HP) was represented through a comprehensive methodology consisting of a structured raster database. A calibrated and validated hydrological model (Soil and Water Assessment Tool—SWAT) was used to estimate monthly streamflow as the Mesh Sweeping Approach (MSA) driver. The methodology was applied for the upper part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 47 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…The sixth paper of this Special Issue, by Alcalá et al [6], proposes a method for automated assessment of Small Hydro-Power (SHP) potential for a run-of-river (RoR) scheme using GIS. Results showed that the headrace's length represented a significant contribution to hydro-power potential estimation.…”
Section: Overview Of the Articles In This Special Issuementioning
confidence: 99%
“…The sixth paper of this Special Issue, by Alcalá et al [6], proposes a method for automated assessment of Small Hydro-Power (SHP) potential for a run-of-river (RoR) scheme using GIS. Results showed that the headrace's length represented a significant contribution to hydro-power potential estimation.…”
Section: Overview Of the Articles In This Special Issuementioning
confidence: 99%
“…A bi-level optimization scheme was used, and a hydropower model called Run-of-River Project Optimization (RORPO) was developed and validated in the Mamquam River Watershed by [27]. An approach of dividing a watershed area into rectangular meshes and determining the potential hydropower site based on the headrace and penstock parameters was proposed and applied to the Huazuntlan river watershed by [42]. Another model based on the GIS and Best-Worst statistical techniques was developed to determine the potential sites for ROR hydropower plants, and the model was compared to field data, upon which, 11 potential sites were detected in the Fomanat plain in Iran [28].…”
Section: Introductionmentioning
confidence: 99%